فقه التعايش والوحدة عند الشيخ خلفان بن جميل السيابي: من خلال أجوبة الفقيه - السيابي, عبد الله بن راشد (مكتبة خزائن الآثار, 2017)
Keywords: Tolérance religieuse – Oman

Je demande à mon gouvernement de tirer parti de l'expérience du Sultanat d'Oman dans le domaine de la tolérance et des droits des femmes - Joxe, Pierre (La femme omanaise sur le chemin de la parité, 2019)
Keywords: Tolérance religieuse – Oman

The undecided Sultanate: tolerance, challenge and sovereignty - Kronenwerth, Dorian (2015)
Keywords: Tolérance religieuse – Oman

Oman, Terra Di Dialogo - Zoja, Federica (Ispi, 2016)
Keywords: Tolérance religieuse – Oman

Un autre modèle que Daech sur le ''marché du religieux'' planétaire ? - Jarry, Frédéric (Le Vif, 2015)
Début avril 2015 se sont tenues les conférences annuelles sur le droit islamique à Mascate, capitale du petit Sultanat d'Oman. L'occasion de découvrir la foi ibadite, ancrée solidement dans une culture, une histoire et une structure politique, certes ferme, mais dont la stabilité et la tolérance augurent de la possibilité d'un "autre" islam dans le "marché des religions" actuel.
Keywords: Tolérance religieuse – Oman

‘The Land of Security’: Western Perceptions of Religious Tolerance in Oman - Hajri, Hilal al- (British Journal of Arts and Social Sciences, 2013)
Oman in 1970, with the advent of Sultan Qaboos bin Said to power, became a modern country. The Sultan worked on the establishment of a civil state based on the foundations of citizenship, equality and social justice. Education, health, human services and government positions, are available to all Omanies, regardless of their origins and sects. He also ordered the issuance of a cultural journal entitled Al-Tasamoh (tolerance), which began publication in 2003. Its main objective was to promote understanding and brotherhood among international societies. Religious tolerance, as we shall see in this paper, is deeply rooted in the Omani culture. This paper explores Western perceptions of religious tolerance in Oman. In the writings of Western travellers and missionaries, the theme of 'tolerance' will be traced.
Keywords: Tolérance religieuse – Oman

Islam et tolérance : à propos d’une exposition omanaise itinérante - Bonnefoy, Laurent (Observatoire, 2019)
Keywords: Tolérance religieuse – Oman

Quand un ministre du culte musulman loue le concile Vatican II... à Oman - Sassine, Georges (La Croix, 2014)
Keywords: Tolérance religieuse – Oman

Religious tolerance in Oman: addressing religious prejudice through educational intervention - Sadi, Fatma H. al-; Basit, Tehmina N. (British Educational Research Journal, 2012)
Keywords: Tolérance religieuse – Oman

Developing Tolerance and Conservatism: A Study of Ibadi Oman - Elliott, Connor D. (UCLA Journal, 2018)
This thesis analyzes the development of Omani-Ibadi society from preIslam to the present day. Oman represents an anomaly in the religious world because its Ibadi theology is conservative in nature while also preaching unwavering tolerance. To properly understand how Oman developed such a unique culture and religion, it is necessary to historically analyze the country by recounting the societal developments that occurred throughout the millennia. By doing so, one begins to understand that Oman did not achieve this peaceful religious theology over the past couple of decades. Oman has an exceptional society that was built out of longtime traditions like a trade-based economy that required foreign interaction, long periods of political sovereignty or autonomy, and a unique theology. The Omani-Ibadi people and their leaders have continuously embraced the ancient roots of their regional and religious traditions to create a contemporary state that espouses a unique society that leads people to live conservative personal lives while exuding outward tolerance.
Keywords: Tolérance religieuse – Oman

أثر الفقه العماني في السلوك المجتمعي :‏ ‏التسامح نموذجا - خماش, نبال; النوفلي, أحمد بن مبارك (بيت الغشام, 2017)
Keywords: Tolérance religieuse – Oman

Religiöse Toleranz: eine Vision für eine neue Welt =: Religious tolerance: a vision for a new world - Salmi, Abdullah Bin Mohammed al (Georg Olms Verlag, 2016)
Keywords: Tolérance religieuse – Oman

Der ibaditische Islam als Modell einer islamischen Toleranz? - Renz, Andreas (CIBEDO-Beiträge zum Gespräch zwischen Christen und Muslimen, 2018)
Keywords: Tolérance religieuse – Oman

Ethnic, Linguistic, and Religious Pluralism in Oman: The Link with Political Stability - Ismāʿīlī, Aḥmad (AlMuntaqa, 2018)
This study examines pluralism and its impact on the political and religious balance in Omani Society, whether religious, linguistic, ethnic, and confessional pluralism or geographical and cultural pluralism. It frames the issue within its geographical and historical contexts and provides an anthropological account of structural patterns in a Gulf state which has rarely been studied. The research will observe three types of discourse, each of which attempts to redefine the components of Omani society and culture. The religious discourse and its significant effect on religious tolerance is the most dynamic discourse. In this context, the convergence of sectarian religious discourse in Oman will be discussed along with the extent to which the Omani Sultanate is influenced by the widespread sectarianism in the Greater Middle East today. The cultural discourse will also be discussed in its contemporary modern form, despite being structurally, sociologically, and politically incomplete. Finally, the paper also explores political discourse and its consolidation of pluralism as a concept in Omani society.
Keywords: Tolérance religieuse – Oman

Ibāḍism and the Tradition of Tolerance in Oman - Sheline, Annelle R. (Oman, Ibadism and modernity, 2018)
Keywords: Tolérance religieuse – Oman

Religious Tolerance in Oman and Ibāḍī Islam - Propst, Amanda (Oman, Ibadism and modernity, 2018)
Keywords: Tolérance religieuse – Oman

Tolerance, Sincerity and Hospitality, as Experienced by European and American Travelers Visiting Oman in the 19th and 20th Centuries - Ḥusaynī, Sulaymān ibn Sālim ibn Nāṣir (Oman, Ibadism and modernity, 2018)
Keywords: Tolérance religieuse – Oman

The Roots of Religious Tolerance in the Omani-Ibāḍī Tradition - Gaiser, Adam R. (Oman, Ibadism and modernity, 2018)
Keywords: Tolérance religieuse – Oman

A Basis for Oman’s Religious Tolerance: A Review of the Late 19th and Early 20th Century Ibadi Jurisprudence of Nūr al-Dīn al-Sālimī from Oman and Muḥammad Aṭfayyash from North Africa Regarding Coexistence with Jews and Christians - Leonard, Douglas R. (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Atfiyyash; Muhammad b. Yusuf (1821-1914); Tolérance religieuse – Oman

The Origins and Contemporary Approaches to Intra-Islamic and Inter-Religious Coexistence and Dialogue in Oman - Leonard, Douglas R. (The Muslim World, 2015)
Keywords: Tolérance religieuse – Oman